KORELASI ANTARA EKOSISTEM MANGROVE Rhizophora stylosa. TERHADAP BIOTA AQUATIK DI PULAU PRAMUKA KEPULAUAN SERIBU - Muzani Jalaludin; Dianti Lestari; Marisa Andriani; Miftahul Ulum; Sri Nurviana Mellenia (JURNAL GEOGRAFI, 2020)
Pramuka Island is one of many islands in Kepulauan Seribu, which is the central government of Kepulauan Seribu Regency and part of DKI Jakarta Province. Aside as government center, Pramuka Island is also as rehabilitation center for mangrove ecosystems located in Taman Nasional Kepulauan Seribu (TNKpS). Mangrove ecosystems become a transition zone between terrestrial ecosystems and marine ecosystems in maintaining biological balance in coastal ecosystems. As a biological function, mangroves have a role as a chain in a waters that can support the life of various types of aquatic biota. Not only that, mangroves can also create a good life for aquatic biota and also contribute greatly to balancing the biological cycle in a waters. As in biological functions, mangrove ecosystems have a role as "aquatic biota habitat" and feeding grounds, nursery and spouning ground for various types of aquatic biota. Rhizophora stylosa is species of endemic mangrove in Pramuka Island. Mangrove forest ecosystem is a habitat for marine organisms which are mostly dominated by mollusks and crustaceans. Mollusks consist of Gastropods are dominated by Potamidae and Ellobiidae species, as well crustaceans which mainly consist of Brachyura spesies, also there are another aquatic biota seems like shrimps, cendro fish and juvenile fish spesies. A research of the correlation between Rhizophora stylosa mangrove ecosystems with aquatic biota in Pramuka Island, Kepulauan Seribu was carried out on 6-7th December 2019. The research used descriptive analysis method. Data which is used in addition to data obtained in the field also includes supporting articles.